PEMANFAATAN INSTANT MESSAGING UNTUK APLIKASI PEMBELAJARAN MEMBACA AL-QUR’AN DENGAN METODE TSAQIFA - Faraz Muhammad Aulia; Made Sudarma; I Made Arsa Suyadnya (SINTECH (Science and Information Technology) Journal, 2019)
Indonesia is predominantly Muslim country. However, around 54% of Muslims cannot read the Qur'an. Many teenagers and adults argue that this is due to lack of time, shame to learn, not having a teacher and so on. Based on these problems, many methods are formulated to help the community in learning. The Tsaqifa method is one method that is claimed to make people able to read the Qur'an in just 7.5 hours. However, along with technological advances, this method began to be considered conventional. Therefore, there needs to be a new alternative so that learning methods can keep up with technological advances. Utilization of instant messaging can be used as an alternatives to implement existing learning methods especially Tsaqifa method that is expected can help communities learn independently, quickly, easily and interactively. In this study, the application of the Tsaqifa method was carried out by developing an application of chatbot in learning the Al-Qur'an reading media that utilizes the LINE Messaging API. Applications that have been built are tested with 2 methods that is Blackbox Testing and System Usability Scale (SUS). In testing using Blackbox Testing, the overall functionality of the application has been declared successfully run and based on the results of the System Usability Scale (SUS) test, obtained an average score of 73.3 out of 20 respondents which means the application can be accepted by the public (acceptable).